Entrepreneurship Preference among University Students: an Evidence of Entrepreneurship Education Program - Purusottama, Ambara; Akbar, Teuku Fajar (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This study aims to answer the effectiveness of EEP toward entrepreneurial preference in Indonesia. Entrepreneurship Education Program (EEP) has become one of the main instruments of growth of many governments around the world, including the Indonesian government. Nevertheless, polemics and debates have arisen in Indonesia regarding its implementation effectiveness. Through this study, we also emphasize the utilization of family (parentsâ€™) work background to understand the effectiveness of EEP further.Â Surveys among university students were conducted in this research, particularly to those who were exposed to EEP during their studies. By using the Theory of Planned Behavior (TPB), the findings conveyed that EEP is indeed effective and in line with studentsâ€™ entrepreneurial preferences. Of the three factors, only subjective norms have a contradicting relationship. Similar results occur using family work background, i.e., families with entrepreneurial-work backgrounds and families who do not have an entrepreneurial-work background. This research contributes to the behavioral theory, particularly in mitigating EEP polemics among researchers and practitioners, as well as assess the effectiveness of EEP.